Retrenchment and its Impact on the Morale of Employees - Sattar Radhi Abid (Scholars Digest Publishing, 2023)
This research aims to know the impact of retrenchment in its five dimensions (administrative procedures, support program, selection criterion, communication channels, job security) on the morale of employees using the data collected from the sample size of 104 who work in private banks in Al-Diwaniyah Governorate. It was found that the retrenchment had an effect on the morale of employees surviving the retrenchment process and the data were analyzed using the multiple linear regression equation. The practical results of the research indicated the significant impact of the retrenchment on the morale of employees.
Keywords: Retrenchment, the morale of employees.